Forms and Functions of Illocutionary Speech Acts in the Film The Imitation Game - Warsidi Warsidi; Rasmawati; Nur Muthmainnah Halim (English Literature Studi Program Universitas Islam Makassar, 2023)
This research aims to determine the forms of illocutionary speech acts contained in the film and to find out their functions using a qualitative method and Searle’s (1969) theory. To obtain data, the researchers watched the film while reading the scripts. The results of the analysis show five forms of illocutionary speech acts in the film The Imitation Game, namely the assertive, directive, commissive, expressive, and declarative forms. This finding indicates that illocutionary speech acts are always more inclined to orders in the directive form. This finding implies that the dialogues mostly contain a direction to do something about what the speaker says. Then, based on the form, fifteen functions of illocutionary speech acts were found in this film, including stating, complaining, reporting, ordering, begging, giving advice, asking, promising, offering something, blaming, congratulating, apologizing, thanking, praising and dismissing. This finding shows that humans, as social beings, always need the help of others to solve the problems they face. It is in accordance with the story from the film, where several characters in this film have tasks that are difficult to solve on their own, one of which is solving the Enigma code. Therefore, they ask a lot of help from co-workers to complete the tasks they face.